Analyzing Recent Seismic Activity of the Opak Fault System in Central Java, Indonesia, From 2009 To 2021 - Ekarsti, Ayu Krisno (GEOMATE International Society, 2023)
A strong earthquake occurred on May 26, 2006, at 22:53:58 UTC, with a magnitude of Mw6.4. The shock was felt with an intensity of VI-VII MMI around Yogyakarta, Indonesia. The earthquake was presumably caused by the movement of the Opak Fault. Following the strong earthquake, seismic activity along the fault has remained high to this day. In order to explain the progression of seismic activity and understand the mechanism of the Opak fault, we conducted catalog relocation, focal mechanism inversion, and statistical analysis of the earthquake events from 2009-2021. The events were relocated using the Double Difference Method. To improve the accuracy of the focal mechanism inversion, we updated the 1-D velocity model from Crust 1.0 to a local velocity model. We inverted the mechanism of earthquakes with a magnitude of Mâ¥3.0. The results indicate that the recent hypocenters are clustered in the southeastern part of the Opak Fault. This cluster is located within the rupture zone of the Mw6.4 2006 mainshock, providing further evidence that post-earthquake deformation from 2006 is still ongoing and primarily involves left-lateral oblique-slip faulting. The mechanism results are consistent with the observable morphological contrast on the surface. Cross-section plots of seismicity and dip angle, perpendicular to the mainshock strike, reveal a flower structure pattern, indicating a complex mechanism. The fault system is believed to be in the interseismic period, supported by the low b-value. The suspicion is further strengthened by an increase in microseismic activity and a decrease in M>3.0. This evidence suggests that the Opak Fault is currently experiencing strain accumulation. © Int. J. of GEOMATE All rights reserved, including making copies, unless permission is obtained from the copyright proprietors.